Religious landscapes, places of meaning: the religious topography of Arcadia from the end of the bronze age to the early Imperial period - Baleriaux, J (2015)
The thesis examines the religious topography of Arcadia through two particular aspects: the built and the natural landscape, and how each relates to human communities, their places of living, and their understanding of the world around. It relies on the assumption commonly made in the field that, since ritual practice was of prevalent importance for the Greeks, cult sites are the most important places for the communities, and therefore they can tell us a lot about the people who built, visited and looked after them. The first part rests on the acknowledgement that sanctuaries are places of interaction for a certain community of cult (which can but need not overlap with a given polis) and explores how they can be indicators of social change, defined here as responses to changes with large impact on the human milieu. These changes and their response articulated in sacred space are identified in four chapters. The first sets the stage and surveys the known sacred sites of Arcadia at the end of the Bronze Age and during the Early Iron Age. The second looks at how the building of temples after the eighth century indicates a significant change in the way communities were structured in Arcadia. The third looks at how Arcadian sanctuaries responded to the increased religious mobility of the Classical and Hellenistic period. Finally, chapter four evaluates the impact of the Roman conquest on Arcadian religious sites. The second part explores how myths and rationalising discourses allowed the Greeks to make sense of the salient characteristics and numen of their surrounding natural landscape. Each of the three chapters departs from a situation observed in Arcadia by ancient sources and examines the responses articulated to explain it. Among the variety of topics to pursue, three have been selected because they exemplify a typical characteristic of Arcadia: its wetness. They also allow spatial areas that were less prominent in part one to be explored. The first chapter investigates the attribution of Mycenaean waterworks in Arcadia to Herakles in myth. The second chapter examines the connection made in ancient sources between Poseidon’s lordship over the Peloponnese, earthquakes, floods and cults of Poseidon Hippios in Arcadia. Finally, the last chapter explores the apparent contradiction of having infernal rivers observable in the world of the living, such as the Styx flowing in the Aroania Mountains.